Clinical Features and Survival Outcome of Early-Stage Primary Pulmonary MALT Lymphoma After Surgical Treatment - Xu, Ye; Zheng, Min; Guo, Qingkui; Wang, Ning; Wang, Rui (Frontiers in Surgery, 2021)
Background: We aimed to study the clinical features and survival outcomes of patients with early-stage primary pulmonary mucosa-associated lymphoid tissue (MALT) lymphoma who underwent surgery. Methods: This is a retrospective, single-center study including 32 patients with early-stage primary pulmonary MALT lymphoma. Univariate and multivariate Cox analyses were performed to select independent prognostic factors. The overall survival (OS) was analyzed by the Kaplan-Meier method and was compared with the log-rank test. Results: Among the 32 patients included, there were 16 men (50.0%) and 16 women (50.0%). The average age was 59.2 years old. Ten patients had non-specific clinical symptoms including cough, expectoration, and chest pain, and four patients had B symptoms. CT images are not specific and can be shown as peripheral, central, solid, and ground glass but more peripheral (93.8%) and solid (75.0%). In prognostic analysis, univariate analysis showed that tumor stage and size were associated with relapse-free survival (RFS) and OS [hazard ratio (HR) = 1.105, 95% CI: 1.021–1.197, P = 0.011; HR = 1.211, 95% CI: 1.158–1.968, P = 0.003, respectively]. It seems to indicate that higher stage and larger size indicate a worse prognosis, but we could not find statistically significant predictors in multivariate analysis. Sublobectomy was performed in 21 (65.6) cases, lobectomy was performed in the other 11 (34.4) cases, both of them can achieve good prognosis (5-year RFS and OS are both 100%), and there is no significant difference between them. Conclusions: The clinical manifestation of early-stage primary pulmonary MALT lymphoma is not significantly specific, and surgical resection is an effective treatment.